Characterization of thermal transport properties of Ag/BaTiO3 composites using hot disk: Numerical simulations. (January 2018) - Xing, Junwei; Muliana, Anastasia; Radovic, Miladin
Highlights: Characterization of thermal transport properties of heterogeneous materials. Numerical simulation at microscopic scale to mimic hot-disk experiments. Investigation of the effect of microstructural size and heat source geometry. Determination of effective thermal properties of composites. Abstract: In this study, a micromechanics model was considered for simulating transient heat transfer response and predicting various thermal properties, such as thermal conductivity, thermal diffusivity and heat capacity, of composite materials, mimicking the hot disk experimental technique. The micromechanics analyses can give insights with regards to variations in the field variables, i.e. temperature and heat flux, in the hot disk experiment for composite materials. The micromechanics model was generated by randomly placing reinforcement particles within a square matrix medium. The effects of heat source geometry were studied, and the convergence behavior in particle size was investigated. These investigations reveal that, the size of the reinforcement particles should be small relative to the hot disk sensor to extract enough information in characterizing the homogenized material properties of the composite in the hot disk experimental technique. To study the effects of small perturbation in input data on the estimation of the material constants, sensitivity analysis was conducted. Both sensitivity analysis and micromechanics model predictions showed that the prediction accuracy for the effective thermal conductivity is higher than that for effective thermal diffusivity. This conclusion is equivalently applicable to the experimentally measured effective properties obtained by the hot disk technique. The newly presented micromechanics model was used to predict the various effective thermal properties of silver/barium titanate (Ag/BaTiO3 ) composite. The predictions were then compared to both the experimental and numerical results reported in the literature.